Discussion about math, puzzles, games and fun. Useful symbols: ÷ × ½ √ ∞ ≠ ≤ ≥ ≈ ⇒ ± ∈ Δ θ ∴ ∑ ∫ π -¹ ² ³ °

You are not logged in.

- Topics: Active | Unanswered

Pages: **1**

Hi Shekhar,

Here is the solution.

((2/3)^k)n = 1

⇒(2/3)^k = 1/n

⇒(2/3)^k = n-¹

Applying log on both sides.

⇒k log(2/3) = -log n

Multiplying (-) on both sides

⇒k log(2/3)-¹ = log n

⇒k log(3/2) = log n

∴ k = (log n)/(log (3/2))

⇒ k = log n base (3/2)

Shekhar wrote:

Can anyone prove the following....

Given,

((2/3)^k)n = 1

Required to prove,

k is equal to log of n on base 3/2

Pages: **1**